1994
DOI: 10.1021/bi00202a011
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Interaction of Natural Proline-Rich Peptides with Five Different SH3 Domains

Abstract: The interaction of six different proline-rich peptides with five SH3 domains has been investigated by using spectroscopic techniques. These peptides correspond to natural sequences and have been implicated in the interaction of some SH3 domains with other proteins. We have determined the Kd values for all of the possible combinations between the peptides and the SH3 domains. Low specificity and low affinity (> 5 microM) are the most remarkable conclusions from these studies. None of the peptides tested here we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
130
0
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 138 publications
(145 citation statements)
references
References 43 publications
12
130
0
3
Order By: Relevance
“…Third, the homology between DOC-2 and p96/mDab2 is weakened towards the carboxy-terminus of the protein. They both have proline-rich domains in this region which contains multiple SH3 binding motifs Feng et al, 1994;Sparks et al, 1994;Viguera et al, 1994). Since Xu et al (1997) has recently demonstrated that the proline-rich domain of mouse p96/mDab2 can interact with the SH3 domains of Grb2 and reduce the binding between Grb2 and Sos, it will be interesting to examine whether the proline-rich domain of DOC-2 can also interact with these signal transduction molecules in the HOSE cells.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the homology between DOC-2 and p96/mDab2 is weakened towards the carboxy-terminus of the protein. They both have proline-rich domains in this region which contains multiple SH3 binding motifs Feng et al, 1994;Sparks et al, 1994;Viguera et al, 1994). Since Xu et al (1997) has recently demonstrated that the proline-rich domain of mouse p96/mDab2 can interact with the SH3 domains of Grb2 and reduce the binding between Grb2 and Sos, it will be interesting to examine whether the proline-rich domain of DOC-2 can also interact with these signal transduction molecules in the HOSE cells.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate the affinity and selectivity of C⌬4, the high-affinity 11-residue peptide p85␣-2 and the lowaffinity 13-residue peptide p85␣-1 were selected as target ligands (15). Both peptides were obtained commercially (United Biochemical Research, Seattle) and used without further purification.…”
Section: Methodsmentioning
confidence: 99%
“…3). In contrast, the latter spectral transition gives rise to a weakly positive band at 225 nm for Ac-RALPPLPRY-NH2, indicative of polyproline II helical conformation with trans Xaa-Pro bonds [27][28][29][30][31][32]. Similarly, Fig.…”
Section: Structural Properties Of Peptides 1--5mentioning
confidence: 98%